RUNOFF HARVESTING FOR IRRIGATION IN RAINFED AREAS - Varma, Vasudeo (Journal of Soil and Water Conservation, 2022)
Water harvesting buadhies are the cheapest source of moisture conservation and irrigation in rainfed micro-watersheds. Besides providing life saving irrigation to crops, it can be used for fisheries development with viable economy. Constructed at suitable sites, these bundhis can command, a large area with increased productivity of major crops. An increase of 73 to 281 per cent in the productivity of various crops and 56 per cent increase in cropping intensity makes these bundhis, a popular and cheap water storage structure to be constructed in rainfed areas.